Multi-criteria decision making for 1.5 MW wind turbine selection - Sagbansua, Lutfu; Balo, Figen (Elsevier Science Bv, 2017)
Climate change and global warming have increased the awareness of mankind in protecting the world. Wind energy is a favorable alternative to conventional fuels for providing clean and cheap energy. For efficient design of wind station project, the best wind turbine selection plays a noteworthy role in the all life cycle. In this paper, AHP method is utilized on the decision of selection for the best wind turbine among turbine brands for 1.5 MW. The selection of the best turbine from several of different turbine brands is complicated task since a few decision criteria need to be noted simultaneously. In this study, the selected turbines are investigated in detail. Based on the experts' opinions, the obtained results by this way are evaluated from technical, economic, environmental and customer attributes by AHP. (C) 2015 The Authors. Published by Elsevier B. V.
8th International Conference on Advances in Information Technology (IAIT) -- DEC 19-22, 2016 -- Macau, PEOPLES R CHINA
Keywords: Renewable energy; Analytic Hierarchy Process; Multi-criteria evaluation; Wind energy